2022
DOI: 10.1371/journal.pone.0266631
|View full text |Cite
|
Sign up to set email alerts
|

How do traditional media access and mobile phone use affect maternal healthcare service use in Bangladesh? Moderated mediation effects of socioeconomic factors

Abstract: Background Exposure to traditional media (TV, radio, and newspapers) and the use of mobile as an interpersonal communication tool allow for a variety of information provision. The purpose of this study is to investigate how women’s media and mobile access affect maternal health service (MHS) utilization. The study also aims to look into the moderated mediation effects of socioeconomic variables on the association mentioned above. Methods The study analyzed reproductive and media data of 5,011 ever-married wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…All studies were based on LMICs of either Asia or Africa. Out of 25 included pieces of literature, nine were undertaken in India [ 7 , 21 28 ], three in both Bangladesh [ 16 , 29 , 30 ] and Nigeria [ 6 , 10 , 31 ], and one each from Afghanistan [ 32 ], Congo [ 33 ], Madagascar [ 34 ], Malawi [ 35 ], Pakistan [ 36 ], Timor-Leste [ 37 ], and Uganda [ 38 ]. The other three studies were multinational, including countries from Asia [ 39 ], Africa [ 40 ], or both [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…All studies were based on LMICs of either Asia or Africa. Out of 25 included pieces of literature, nine were undertaken in India [ 7 , 21 28 ], three in both Bangladesh [ 16 , 29 , 30 ] and Nigeria [ 6 , 10 , 31 ], and one each from Afghanistan [ 32 ], Congo [ 33 ], Madagascar [ 34 ], Malawi [ 35 ], Pakistan [ 36 ], Timor-Leste [ 37 ], and Uganda [ 38 ]. The other three studies were multinational, including countries from Asia [ 39 ], Africa [ 40 ], or both [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…A 2021 study that analyzed a dataset from nine countries between 2013 and 2017 found that watching television and reading newspapers had positive relationship with institutional delivery in sub-Saharan Africa [ 17 ]. Likewise, a study conducted in South Asian countries, including India, Bangladesh, Nepal, and Pakistan, identified a positive link between mass media exposure and the use of maternal healthcare services, such as an increased likelihood of giving birth in a healthcare facility [ 8 , 18 ]. Comparable studies conducted in resource-limited settings in Africa, such as Ethiopia and Uganda, also highlighted a positive association between women’s exposure to television, radio and newspapers and their use of maternal health services.…”
Section: Discussionmentioning
confidence: 99%
“…Our research also reported that women who have their own mobile telephones are less likely to face barriers to access to healthcare. A previous study showed that mobile phone use and media access are associated with the use of maternity health services [40]. Owning a mobile telephone is one of the ways to arrange transportation in an emergency [41] and access health information, engage with health practitioners, and provide quality health services.…”
Section: Plos Onementioning
confidence: 99%